Applying strain gauges to measuring thermal warpage of printed circuit boards. (November 2017) - Huang, Chien-Yi; Ying, Kuo-Ching
Abstract: Printed circuit boards (PCBs) are composite structures consisting of FR-4, solder mask, and Cu materials. When heated during reflow, these materials exhibit different levels of expansion because of their dissimilar thermal expansion coefficients. Currently, the shadow moiré method is the primary means for measuring PCB warpage. However, applying this method to soldered PCBs can yield inaccurate warpage data because of differences in component height. Moreover, flux volatilization during reflow can pollute the gratings of shadow moiré measurement systems. However, the PCB packaging industry rarely adopts this method because budget constraints, leading to low process quality caused by PCB deformation during reflow. By employing a 3-axis strain gauge measurement technique, this study developed a low-cost PCB warpage measurement method that yields accurate PCB warpage data despite considerable differences in component height and flux volatilization during reflow. Multiple process parameters (e.g., reflow soldering temperature) were employed to analyze bare and soldered PCBs to verify the feasibility of the proposed method by evaluating various PCB characteristics before, during, and after reflow.